The Role of Oxidative Stress in Sarcoidosis - Sara Solveig Fois (MDPI AG, 2021)
Sarcoidosis is a rare, systemic inflammatory disease whose diagnosis and management can pose a challenge for clinicians and specialists. Scientific knowledge on the molecular pathways that drive its development is still lacking, with no standardized therapies available and insufficient strategies to predict patient outcome. In recent years, oxidative stress has been highlighted as an important factor in the pathogenesis of sarcoidosis, involving several enzymes and molecules in the mechanism of the disease. This review presents current data on the role of oxidative stress in sarcoidosis and its interaction with inflammation, as well as the application of antioxidative therapy in the disease.